2017
DOI: 10.1177/1475725717725493
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Knowledge About Intellectual Giftedness: A First Look at Levels and Correlates

Abstract: Evidence-based knowledge about intellectual giftedness is important for identifying, counseling, and fostering intellectually gifted students. How much teachers actually know about intellectual giftedness is unclear because previous studies have relied solely on self-reports. This study aimed to: (a) develop a test for the assessment of teachers' knowledge about intellectual giftedness defined as an intellectual capacity significantly above average, the identification of giftedness, and characteristics of gift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 59 publications
8
34
0
5
Order By: Relevance
“…For non-experts, this is unsurprising because it is not realistic for them to be aware of the research in an interdisciplinary scholarly field. The results in the teacher sub-sample, though, are in line with Heyder et al's (2018) results that showed that most teachers had low levels of knowledge regarding the nature, manifestations, and correlates of intellectual giftedness.…”
Section: General Interpretation Of Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…For non-experts, this is unsurprising because it is not realistic for them to be aware of the research in an interdisciplinary scholarly field. The results in the teacher sub-sample, though, are in line with Heyder et al's (2018) results that showed that most teachers had low levels of knowledge regarding the nature, manifestations, and correlates of intellectual giftedness.…”
Section: General Interpretation Of Resultssupporting
confidence: 86%
“…Among the entire sample, 33.9% of teachers' responses and 29.4% of non-teachers' responses were empirically supported (using the information in Table S8 as a standard). This is similar to the Heyder et al's (2018) study showing that teachers' viewpoints about intellectual giftedness were correct for 26.8% of items on their survey.…”
Section: General Interpretation Of Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In other contexts, e.g., intellectual giftedness (e.g., Heyder et al 2018), it has been found that some topics are not sufficiently treated in teacher education and need to be addressed more to ensure an adequate level of knowledge. Motivation might be another example of the current debate on a lack of connection between the different phases of teacher training (link between theory and practice, see, e.g., Vogel 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%